The Süleymaniye Mosque and the Taj Mahal: A comparative study of two outstanding paradigms of Islamic Art - Islam, Arshad (B.R. Publishing House, New Delhi, 2021)
The Süleymaniye Mosque and the Taj Mahal were built nearly a century apart—one during 1550-1557, the other during 1632-1652—and geographically in two far-off places—the one in Istanbul, Turkey, the other in Agra, India. These specimens of Islamic architecture outshine not only buildings of their own times but those since. In the case of Süleyman I’s mosque, the architect’s identity is not open to doubt: Sinan, a Greek janissary, had risen through the ranks to be given the office of the chief architect of the mosque project. In the case of the Taj Mahal, the identity of the chief architect has long been open to debate, but the most plausible explanation is that the family of engineers behind the Taj are as identified based on the discovery of Diwan-i-Muhandis, a book in Persian verse by Lutfullah Muhandis, one of the three engineer sons of Ustad Ahmad Lahori (d 1059/1649). The family moved to Delhi and built Shahjahanabad, the new capital outside Old Delhi, which has left landmarks like the Red Fort and the Jama Masjid. Although the available literature hints at a possible linkage between the architects of the two structures, the connection remains tenuous. The present paper highlights and clarifies the linkage through the use of architectural descriptions of the masterpieces of the two architects and also through biographical evidences to compare and contrast the meanings of the Süleymaniye Mosque and the Taj Mahal.